Combining Ozonation and Ceramic Membrane Filtration for Tertiary Treatment. Issue 8 (8th May 2013) - Stüber, Johan; Miehe, Ulf; Stein, Robert; Köhler, Mirco; Lesjean, Boris; Wessling, Matthias
Abstract A pilot plant with a full scale monolithic ceramic membrane was operated at Ruhleben wastewater treatment plant (WWTP), Berlin Germany, for more than 12 months. Filtration performance according to the applied pre‐treatment (dose of ozone and coagulant) were investigated. Trial runs with and without ozone, varying the operational parameters such as flux, coagulant dosage, and filtration time were conducted in order to identify the benefits of pre‐ozonation. The reduction of the total fouling rate by ∼70 % when applying a specific ozone dose between 1.0 and 1.4 mg O 3<inline-graphic xlink:href="ark:/27927/pgg276zvw9v" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> mgDOC–1 highlights the potential of ozonation as pre‐treatment step. Using LC‐OCD measurements, the effect of ozone on the biopolymer concentration and the DOC fraction was demonstrated.